A Text Book Of Agri-Business Management - A.C. Broadway; Arif A. Broadway (LUDHIANA KALYANI, 2002)
This book provides agri-business and its management.
Management farms Livestock management Agricultural product
Keywords: Management farms, Livestock management, Agricultural product